Gastroesophageal reflux: clinical presentations, diagnosis and management. - Waterfall, W E (1986)
Symptomatic gastroesophageal reflux occurs daily in an estimated 7% of adults and weekly or monthly in 29%. Untreated it can lead to esophageal erosions, ulceration and stricture formation. The pathogenesis is often multifactorial: defects in the function of the lower esophageal sphincter, esophageal clearance mechanisms and gastric emptying combine to produce frequent lengthy periods during which the lower esophagus is bathed in regurgitated acid. In most patients reflux disease is easily recognized as recurrent heartburn, regurgitation or dysphagia, or a combination. When acute chest pain or respiratory illness is the primary presenting complaint the patient needs particularly careful investigation to determine whether the symptoms are due to a primary cardiac or respiratory condition, are secondary to gastroesophageal reflux alone or represent a combination of disorders. Endoscopy with biopsy and long-term pH monitoring are the most reliable ways of determining whether reflux disease is present. Additional investigations, such as exercise testing, cardiac catheterization or inhalation challenge, may be needed in patients with cardiac or respiratory symptoms. Treatment should follow a stepped-care approach and in most patients should begin with changes in lifestyle, including dietary manipulation, reducing alcohol and cigarette consumption, and raising the head of the bed, together with appropriate use of antacids or alginate-antacid combinations. H2-receptor antagonists and agents to improve both gastric emptying and the tone of the lower esophageal sphincter may be added in sequence. Most patients will respond well to this regimen. Surgery should be considered only for those with intractable symptoms or with complications (e.g., stricture formation, bleeding, development of dysplastic epithelium in those with Barrett's esophagus, or secondary pulmonary disease that does not respond to medical management). It is successful in 85% of well-selected patients and has few complications.